New dimension on potential factors of successful pediatric peripheral intravenous catheterization - Chun-Hao Chu; Chiung-Chen Liu; Chung-Yu Lai; Ying-Chuan Chen; Chiung-Hsi Tien; Kao-Hsian Hsieh; Chien-Ming Lin (Elsevier, 2023)
Background: Peripheral intravenous catheterization (PIVC) is pivotal to pediatric medical care; however, it is a challenging technique for pediatricians, and the parameters affecting successful pediatric PIVC establishment have not been fully investigated. Methods: This prospective observational study collected data from pediatric patients aged less than 18 years who required PIVC. The participants were categorized into five groups for subgroup analysis: newborn, infant, toddler, pre-school, and student (children and adolescent). Data on demography, biochemistry, and PIVC executors were examined to elucidate the most powerful factors affecting the success of PIVC. Results: A total of 935 peripheral venous cannulations conducted within 1 year were studied. Age-subgroup analysis showed the highest failure rate (FR) of PIVC in the infant group (18.4%). No significant difference in BMI standard deviation score was noted among the groups (p-value = 0.430). Compared with those for the success group, more attempts, longer completion time, and more medical staff were needed for the failure group (all p-values < 0.05). A high serum procalcitonin level was correlated with an increased FR (p-value = 0.016). In addition, the success rate was positively associated with the seniority of the operators, except for the 3-year experienced R3 group (93.5%) showing a higher success rate than the 4-year experienced CR group (84.2%). Conclusions: Difficulty in setting up PIVC was the greatest in infants and even greater than that in newborns. Even though seniority was a cardinal factor in successful PIVC, a high FR was still noted despite the lack of continuous and steady practice.